2014
DOI: 10.1002/qua.24664
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio spectroscopic study for the NaRb molecule in ground and excited states

Abstract: A wide adiabatic study is performed for NaRb molecule, involving 151Σ+ electronic states including the ionic state Na−Rb+, as well as 143Σ+, 1–91,3Π, and 1–51,3Δ states. This investigation is performed using an ab initio approach which involves the effective core potential, the core polarization potential with l‐dependent cut‐off functions. The NaRb system has been treated as a two‐electron system and the full valence configuration interaction is easily achieved. The spectroscopic constants Re, De, Te, ωe, ωex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
35
5

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 66 publications
14
35
5
Order By: Relevance
“…Detailed comparisons with the previous theoretical and experimental results showed a good agreement (see Ref. ). In 2015, Wiatr et al performed an adiabatic investigation on the NaRb system.…”
Section: Methodssupporting
confidence: 78%
See 4 more Smart Citations
“…Detailed comparisons with the previous theoretical and experimental results showed a good agreement (see Ref. ). In 2015, Wiatr et al performed an adiabatic investigation on the NaRb system.…”
Section: Methodssupporting
confidence: 78%
“…They have studied the adiabatic PECs as well the spectroscopic constants ( R e , D e , T ev , T e , ω e , B e , D 0 ) of the first 5 1 Σ + , 5 3 Σ + , 3 1 Π, 3 3 Π, 1 1 Δ, and 1 3 Δ states by means of the nonrelativistic quantum chemical method with an effective, nonlocal pseudopotential for each atom. They performed various comparaisons with our previous much extended study and, despite the rather different ab initio approaches, showed a nice global agreement which gives confidence in our adiabatic results.…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations